Emergency peripartum hysterectomy: a retrospective analysis in a tertiary care hospital in Jharkhand, India - Bhagat, Megha; Moitra, Bratati (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Emergency peripartum hysterectomy (EPH) is a rare but a lifesaving procedure done as a last resort to save life of mother. We conducted this study to know the incidence, leading causes, and complications of obstetric hysterectomy. Methods: Authors conducted a retrospective analysis of all the patients who underwent emergency peripartum hysterectomy from January 2015 to December 2017 at RIMS, Ranchi. Results: There were 126 emergency peripartum hysterectomies, with deliveries during the same period being 21732 and the rate of EPH was 5.7 per 1000 deliveries. Most common indication for EPH was uterine rupture (54.6%), followed by uterine atony (18.2%) and morbidly adherent placenta (23.01%). Most of the patients (66.67%) had previous cesarean deliveries. EPH was done following cesarean in 66.67%. Subtotal hysterectomy was done in 88.09%. Intra-operative urinary bladder injury was seen in 11.11% of the patients. Conclusions: Uterine rupture and Morbidly adherent placenta continues to be the most common causes for EPH in our population. Multiparity is an important risk factor among patients with rupture uterus. Cesarean delivery and repeat cesarean deliveries are the likely risk factors for EPH.